Does Long-Term Exposure To Robots Affect Mind Perception? An Exploratory Study. (December 2020) - Kim, Min Ji; Kohn, Spencer; Shaw, Tyler
From cleaning houses to assisting airport passengers, robots are rapidly becoming an integral part of society. As they transition into a facet of the everyday environment, it's important to understand how beliefs and behavior concerning these robots will change over time. While human-robot interaction research is common, there is a significant literature gap concerning long-term interaction with these agents. The current study seeks to better understand how exposure over a time-scale of months changes mind perception towards robots. This area of research is especially critical given that mind perception has been shown to influence behavior. A fortuitous deployment of robots across the authors' university campus provided an unprecedented opportunity to study this interaction via a naturalistic experiment.